Desain Arsitektur Pusat Perbelanjaan dan Fenomena Masyarakat Konsumen - Laksmi Kusuma Wardani (Ars: Jurnal Seni Rupa dan Desain, 2012)
dern architectural designs tend to looksimilar. Tey are buit in massive forms withsimple geometry and perform structural andfunctional aesthetic values that show the mixtureof mechanical aesthetic elements and economicalaesthetics engineering. Te fact that there are a bignumber of shopping malls built in numerous citiesin Indonesia is the physical evidence of the moderndesign. It also indicates that consumerism culturegrows quickly in the pluralistic urban sociey